Audit of BPK RI Performance on the Cooperation Scheme Agreement between the Government and Business Entities (KPBU) - Irdham Riyanda (Fakultas Hukum Universitas Lampung, 2020)
The scheme of the Government Partnership Agreement with Business Entities (KPBUS) or known as the Public Private Partnership (PPP). It is a model agreement between the government as the owner of the land and the business entity as the business manager to carry out the socio-economic functions of the government with the size of the rights and obligations attached to each party. The implementation of the PPP agreement cannot be separated from the various legal aspects that underlie it, namely the legal aspects of the agreement, the legal aspects of state land use and the legal aspects of state finance. The existence of this legal aspect of state finance is inherent in the function and authority of BPK RI to conduct an examination of it. The type of inspection that is most appropriate for assessing the series of PPP agreement management processes, from planning to monitoring and evaluation is the type of performance inspection. Furthermore, in conducting a preliminary examination the performance of the examiner is required to be able to identify the problem before carrying out a detailed examination. There are several basic problems described in this paper, starting from the planning process to monitoring and evaluation that need to be followed up by preparing concrete audit steps and a recommendation that can be applied by the institution.